الإشاعة الحربية في زمن الإرهاب بالجزائر المفاهيم والنماذج: نحو قراءة أنثروبولوجية تفسيرية - مروفل، مختار (جامعة حسيبة بن بوعلي بالشلف, 2018)
تتصل ورقتنا بموضوع الإشاعة في زمن الإرهاب الذي عاشته الجزائر خلال العشرية الأخيرة من القرن الماضي، في البداية سنلقي الضوء على الحقل المفاهيمى، والاصطلاحات الأكاديمية الموضحة والمفككة لمعنى الإشاعة التي تطل برأسها أثناء التوترات والأزمات، فتعصف بالمجتمعات في فترات الضعف والنكوص على الأعقاب، نشرح من خلالها الحيثيات الخاصة بالموضوع المطروق ونساهم بها في التأصيل المعرفي، لهذه الظواهر وذلك بتحديد تصور رصين وواضح يستلهم مرجعيته من الدراسات والأبحاث الأكاديمية الكونية. ثانيا سنقدم إشارات عن الزمان وعن المكان، اللذان تتخذ منهما الإشاعة مسرحا لها وكذلك النماذج الميدانية الواردة في هذا السياق، وكيفية تحليلها وتأويلها وتحديد التساؤلات الكبرى المنبثقة من عمق هذه العملية. ثالثا سنعرج على الاستنتاجات الإستخلاصات الممكن التوصل إليها، معقبين في الأخير على خطورة الإشاعة والآثار التدميرية التي يمكن أن تحدثها على مستوى النسوج الاجتماعية والروابط الأساسية لها، الأكثر حميمية ومسؤولية في إنتاج عناصر اللحمة والقوة الخاصة بتماسك المجتمع.
Our paper relates to the theme of the rumor in the era of terrorism that Algeria experienced during the last decade of the last century. In the beginning, we will shed light on the conceptual field, and the articulated academic terminology of the meaning of the rumor that arises during times of crisis. It explodes societies in periods of weakness and fallacy. We explain the rationales of the subject and contribute to the conceptualization of these phenomena by defining a clear vision. Inspired by its reference to global academic studies and research. Secondly, we will provide references on time and place, from which the rumor takes place, as well as the field models presented in this context, and how to analyze and interpret them and identify the major questions arising from the depth of this process. Thirdly, we will review the conclusions and conclusions that can be reached. The latter will be based on the seriousness of the rumor and the destructive effects it can have on the level of the social fabric and its basic ties, the most intimate and responsible in the production of the elements of cohesion and the strength of social cohesion.
Keywords: علم الاجتماع -- الإشاعات -- الجزائر -- الإرهاب -- وسائل الإعلام